Pengembangan Model Sistem Penjaminan Mutu Internal di Pondok Pesantren - Mutia Irmayanti; Ahmad; Rahmat Rosyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The community has the right and responsibility for the existence of quality educational institutions. similar to the regulations contained in Law Number 18 of 2019 concerning Islamic boarding schools that the implementation of an internal quality assurance system absolutely must be carried out well. However, based on the results of research conducted in several Islamic boarding schools in Bogor, we do not fully understand the stages of quality assurance. Several existing Islamic boarding schools have a quality assurance team but they are not the oldest in the organizational structure. This means that the human resources appointed as the quality assurance team include but are not legally formalized in a decision letter, this means that the Islamic boarding school implements quality assurance components but is not implemented administratively. This research aims to first, analyze the need for developing an internal quality assurance system model in Islamic boarding schools. Second, to develop an internal quality assurance system model in Islamic boarding schools. Third, to test the feasibility of the internal quality assurance system model in Islamic boarding schools. The research uses the Research and Development method, using the ADDIE model. The results of the research findings showed that the analysis of the need for developing an internal quality assurance system in Islamic boarding schools was carried out in the first two stages of the field needs analysis consisting of 9 Islamic boarding schools with 11 respondents. The conclusion was that 100% of respondents needed an internal quality assurance system model for Islamic boarding schools to guarantee the quality of education. boarding school. Second, document analysis consisting of internal quality assurance system documents issued by the Ministry of Education and Culture's primary and secondary education, as well as internal quality assurance system regulations issued by law number 18 of 2019 concerning Islamic boarding schools, became a reference in preparing a model for the internal quality assurance system in Islamic boarding schools. . The Islamic boarding school internal quality assurance system model produces a product in the form of the SPMI model in Islamic boarding schools which explains the internal quality assurance cycle including planning the quality of Islamic boarding school education, preparing plans to improve the quality of Islamic boarding schools, implementing plans to improve the quality of Islamic boarding schools, monitoring and evaluating the implementation of plans to improve the quality of Islamic boarding schools, setting standards. new quality and developing strategies to improve the quality of Islamic boarding schools. Third, a one to one test was carried out with educational management experts, linguists and experts in the field of Islamic boarding school with validation test results by experts in educational management of 81%